Biohythane production in two-stage anaerobic digestion system. (28th June 2019) - Hans, Meenu; Kumar, Sachin
Abstract: Hydrogen (H2 ) and methane (CH4 ) are the potential alternative energy carriers with autonomous extensive and viable importance. These fuels could complement the advantages, and discard the disadvantages of each other, if produced simultaneously. Considering their complementary properties, co-production of a mixture of H2 and CH4 in the form of biohythane in two-stage anaerobic digestion (AD) process is gaining more interest than their individual production. Biohythane is a better transportation fuel than compressed natural gas (CNG) in terms of high range of flammability, reduced ignition temperature as well as time, without nitrous oxide (NOx) emissions, improved engine performance without specific modification, etc. Other than production of biohythane, performing two-stage AD is advantageous over one-stage AD due to short HRT, high energy recovery, high COD removal, higher H2 and CH4 yields, and reduced carbon dioxide (CO2 ) in biogas. For improved biohythane production, various aspects of two-stage AD need to be emphasized. Keeping the facts in mind, the process of two-stage AD along with microbial diversity in comparison to one-stage AD has been discussed in the previous sections of this review. For large scale commercial production, and utilization of biohythane in automobile sector, its execution needs evaluation of process parameters, and problems associated with two-stage AD. Hence, the later part of this review describes the production process of biohythane, concerned microbial diversity, operational process parameters, major challenges and their solutions, applications, and economic evaluation for enhanced production of biohythane. Highlights: Two-stage anaerobic digestion process is explored for biohythane production. Benefits of biohythane and its applications are summarized. Key challenges and their solutions are discussed.